2007
DOI: 10.1007/s00436-007-0799-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and larvicidal properties of the essential oils from Drimys brasiliensis Miers (Winteraceae) on the cattle tick Rhipicephalus (Boophilus) microplus and the brown dog tick Rhipicephalus sanguineus

Abstract: The essential oil obtained from leaves and stem barks of the Southern Brazilian native Drimys brasiliensis Miers, a tree with medicinal properties, was analyzed by gas chromatography (GC) and GC/mass spectrometry (MS). The oil was characterized by sesquiterpenoids (66%), cyclocolorenone being the most abundant (30.4%), followed by bicyclogermacrene (11.8%) and alpha-gurjunene (6.0%). Laboratory tests were carried out to determine the toxicity of the essential oil on larvae of the cattle tick Rhipicephalus (Boo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 21 publications
0
30
0
9
Order By: Relevance
“…Those concentrations were all lethal for 100% of larvae. Pulegone was the main compound isolated from the essential oil (RIBEIRO et al, 2010). In addition, tests on this family were carried out using the essential oil from leaves VALENTE et al, 2007;SRIVASTAVA et al, 2008;COSTA et al, 2008;MAGADUM et al 2009;BROGLIO-MICHELETTI et al, 2009 Azadirachtin (BUTTERWORTH; MORGAN, 1971) Salanin (MEISNER et al, 1981) Nimbin, nimbinin (SIDDIQUI et al, 1988) Meliatetraolenone, odoratone (SIDDIQUI et al, 2003) Melia azedarach L. (BORGES et al, 1994(BORGES et al, , 2003VIVAN, 2005;SOUSA et al, 2008).…”
Section: In Vitro Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those concentrations were all lethal for 100% of larvae. Pulegone was the main compound isolated from the essential oil (RIBEIRO et al, 2010). In addition, tests on this family were carried out using the essential oil from leaves VALENTE et al, 2007;SRIVASTAVA et al, 2008;COSTA et al, 2008;MAGADUM et al 2009;BROGLIO-MICHELETTI et al, 2009 Azadirachtin (BUTTERWORTH; MORGAN, 1971) Salanin (MEISNER et al, 1981) Nimbin, nimbinin (SIDDIQUI et al, 1988) Meliatetraolenone, odoratone (SIDDIQUI et al, 2003) Melia azedarach L. (BORGES et al, 1994(BORGES et al, , 2003VIVAN, 2005;SOUSA et al, 2008).…”
Section: In Vitro Testsmentioning
confidence: 99%
“…Over 95% larvae mortality was obtained with the essential oil of Drimys brasiliensis (Winteraceae) at concentrations of 3.125 to 25 µL.mL -1 (≈ 0.3125 to 2.5%). The oil was characterized by sesquiterpenoids, cyclocolorenone, bicyclogermacrene and alpha-gurjunene (RIBEIRO et al, 2008b). The ethanolic extract of seeds of Annona muricata L. (Annonaceae) at a concentration of 2% had 100% efficacy against engorged females (BROGLIO-MICHELETTI et al, 2009).…”
Section: Familymentioning
confidence: 99%
“…Malheiros et al (2005) detected antifungal activity of sesquiterpenes found in the bark of D. brasiliensis, and CechinelFilho et al (1998) isolated and identified several active compounds from its bark, and found that the polygodial was more potent in controlling pain. BARK HARVESTING OF Drimys brasiliensis Ribeiro et al (2008) identified that the essential oils found in the leaves and bark of D. brasiliensis were lethal to dog and cattle ticks.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, several plants have been evaluated against R. (B) microplus, highlighting Melia azadirachta (SOUSA et al, 2008), Azadirachta indica (COSTA et al, 2008), Drimys brasiliensis (RIBEIRO et al, 2008b), Piper aduncum (SILVA et al, 2009), Simarouba versicolor (CATTO et al, 2009), Calea serrata (RIBEIRO et al, 2011), Tagetes minuta (GARCIA et al, 2012) and Guarea kunthiana (BARBOSA et al, 2013).…”
Section: Introductionmentioning
confidence: 99%